Sistem Informasi Geografis Panduan Wisata Berbasis Android di Kota Cirebon - Dion Nugraha; Nana Suarna; Dita Rizki Amalia (INTERNAL (Information System Journal), 2022)
City guide is very important for tourists and nomads in cities that are a source of tourist destinations as well as a source of destination for immigrants both for education or for work, one of which is the city of Cirebon. Based on data collected from the Cirebon City Culture and Tourism Office, in 2019 there were 987,588 tourist visits in Cirebon City. The problem that occurs is that many of the immigrants or tourists are not informed about the places in the city of Cirebon. In this research, a tourist guide geographic information system will be made regarding the information and location of places in the city of Cirebon which can be accessed through their android devices. The method used in the development of this system is the waterfall method. The waterfall method was chosen because in the development process it has a clear work sequence and is also easy to manage because of the simple model. The stages of system development in the waterfall method are Requirements Analysis, System Design, Implementation, Testing and Maintenance. The design of the city guide information system was built using the Java programming language using the Android Studio Integrated Development Environment (IDE), SQL database, and using the Google Maps API feature. The result is an android-based city guide application that contains information and location of places in the city of Cirebon such as tourist attractions, hotels, shopping centers, health services and others. This system will make it easier for tourists because there are recommendations about destinations that can be visited while in the city of Cirebon. It is hoped that the system created can become an information that can support and facilitate the activities of immigrants or tourists while in the city of Cirebon.